Gaya Komunikasi Pemimpin Perempuan: (Studi Camat Bekasi Timur) - Fiqih Akhdiyatu Salam; Iqbal Shamiago (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to examine the communication styles of female leaders in East Bekasi District. The research method used was qualitative with 7 informants, namely 1 sub-district head and 6 sub-district staff. Data collection methods use observation, interviews and documentation. The results of the research show that the East Bekasi Subdistrict Head's communication style uses patterns. The control communication style is used by the sub-district head through instructions and supervision of subordinates. The egalitarian communication style encourages discussion and collaboration between the sub-district head and his staff. The structuring communication style provides clear direction in carrying out tasks. A dynamic communication style motivates aggressive actions to improve performance. The reliquis communication style provides autonomy to subordinates. Communication style is withdrawn, open and involved in communication with subordinates. Withdrawal's communication style is not visible in the communication style of the East Bekasi Subdistrict Head. This communication style involves withdrawal and lack of involvement in communication with subordinates.